Costs and Benefits of Labour Mobility between the EU and the Eastern Partnership Partner Countries. Country report. Belarus - Alexander Chubrik; Alaksei Kazlou (Center for Social and Economic Research (CASE), 2013)
Labour migration does not appear to have the same magnitude and socio-economic importance in Belarus as in other EaP countries. It is one of the few post-socialist economies that have preserved the dominance of the state sector and built complicated systems of subsidisation and economic support for the population designed to manage the political-business cycle (see Chubrik, Shymanovich, Zaretsky (2012)). This model has allowed the economy to grow quite steadily until recently. However, the distorted system of incentives that was created for enterprises and households has resulted in the need for a "correction", which happened in the form of a balance of payments crisis in 2011. The impact of this factor on migration has not been fully visible yet. At the same time the relatively long period of stability and gradual, but steady, increase in welfare payments has played a role as a migration-restraining factor. In order to estimate cost and benefits of labour migration between EU and Belarus, this study utilises publically available literature as background and relies where possible on micro-data: Census-2009, Household Budget Survey (HBS), as well as relevant official data and data from polls related to the topic. Additionally, some sections of this report rely on information collected in the course of a focus group meeting with labour migrants and a series of in-depth interviews with officials from state, international, and non-governmental agencies dealing with migration. Lastly, in some cases anecdotal evidence was collected to support some of the new trends that have not yet been recorded in the statistics.
Keywords: D78; F22; F24; I25; J01; J15; J40; J61; J83; 330; Labour Economics; Labour Markets; Labour Mobility; Belarus